Method for producing cellulose-based moisture-sensitive color-changing material

By using synthetic ionic liquid systems and condensation bath regeneration technology in the manufacturing process of cytoplasm-sensitive chromovariant materials, the problems of low strength and low sensitivity of existing materials are solved, and the color change effect of high strength and high sensitivity is achieved, which is suitable for humidity detection in multiple fields.

JP2025512162AInactive Publication Date: 2025-04-17QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2023578769
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-02-24
Filing Date
2023-09-25
Publication Date
2025-04-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing cytoplasm-sensitive chromovarising materials have low strength and low sensitivity during the manufacturing process, which limits their application and development.

Method used

The pine needle paper pulp is dissolved by a synthetic ionic liquid system, and a cytoplasmic solution is formed by heating and stirring, then regenerated in a condensation bath, and then soaked and dried in a solution containing chromium compounds to produce a cytoplasmic sensitive chromotropic material with high strength and high sensitivity.

Benefits of technology

It improves the physical strength and color change sensitivity of cytoplasmic materials, making it have significant color change effect when detecting different humidity ranges, easy to observe, and simple process and low cost, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512162000001_ABST
    Figure 2025512162000001_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of biomaterial production, and provides a method for producing a cellulose-based moisture-sensitive discoloration material. The softwood kraft pulp is used as raw material, dissolved in a composite ionic liquid dissolving system containing ionic liquid, hydrogen ligand, reinforcing agent and retention agent, and after dissolving the cellulose, different forms of cellulose materials are produced by an extruder or film applicator, and then enters a coagulation bath to be regenerated. In the washing process, the obtained cellulose wet material is immersed in an appropriate concentration of cobalt chloride aqueous solution, and dried to obtain a cellulose-based moisture-sensitive material. The present invention imparts moisture-sensitive discoloration performance to cellulose without increasing the production process, while at the same time increasing strength and reducing costs.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a Chinese patent application filed with the China Patent Office on February 24, 2023, bearing application number CN202310181983.2 and entitled "Method for manufacturing a cellulose-based moisture-sensitive color-changing material," the entire contents of which are incorporated herein by reference.

[0002] The present invention belongs to the field of biomaterial production, and relates to a method for producing a cellulose-based moisture-sensitive color-changing material. [Background technology]

[0003] This background information is disclosed solely for the purpose of enhancing understanding of the general context of the present invention, and is not necessarily considered to identify or in any way suggest that this information constitutes prior art already known to those skilled in the art.

[0004] A moisture-sensitive color-changing material is a material whose structure changes when it absorbs moisture, causing the absorption spectrum of the material to change, and the color of the material to change, exhibiting different colors under different humidity conditions. It has the advantages of being observable with the naked eye and having fast response. Most of the moisture-sensitive color-changing materials at present are made of organic compounds or synthetic compounds, and have disadvantages such as being difficult to decompose, being expensive, and having a complicated manufacturing process.

[0005] Cellulose is a natural polymer that is abundant in nature and can be naturally decomposed and continuously regenerated. Cellulose-based materials have many advantages, such as light weight, good breathability, environmental friendliness, and wide supply sources. Cellulose is a polymer in which β-D-glucopyranosyl is bonded by 1,4-β-glycosidic bonds, and has good water absorption and swelling capabilities due to the presence of many hydroxyl groups and hydrogen bonds between molecules, making cellulose a good choice for manufacturing humidity sensors. At the same time, cellulose's degradability, recyclability, and biocompatibility make it a good choice for replacing fossil raw materials. At the current stage, cellulose-based moisture-sensing materials have disadvantages such as low strength and low sensitivity, which limits the application and development of cellulose-based moisture-sensing materials. Summary of the Invention [Problem to be solved by the invention]

[0006] In order to overcome the above-mentioned shortcomings, the present invention provides a method for producing a cellulose-based moisture-sensitive color-changing material, which is prepared by dissolving softwood kraft pulp as raw material in a composite ionic liquid system, and using an extruder or film applicator to produce different forms of cellulose materials, which are then regenerated in a coagulation bath, and in the washing process, the obtained cellulose wet material is immersed in an appropriate concentration of cobalt chloride aqueous solution, and then dried to obtain a cellulose-based moisture-sensitive material. [Means for solving the problem]

[0007] To achieve the above objectives, the present invention adopts the following technical solutions:

[0008] In a first aspect of the present invention, there is provided a method for producing a cellulose-based moisture-sensitive color-changing material, the method comprising the steps of: The paper pulp and the composite ionic liquid dissolving system are mixed under vacuum at 60 to 75°C for 20 to 30 minutes to dissolve the cellulose, thereby obtaining a cellulose solution; regenerating the cellulose solution to obtain a cellulose wet material; and immersing the cellulose wet material in a cobalt chloride aqueous solution having a concentration of 2 wt% to 25 wt% for 10 to 60 s and drying the material to obtain the cellulose-based moisture-sensitive color-changing material. The composite ionic liquid dissolution system includes an ionic liquid, a hydrogen ligand, a strengthening agent, and a retention agent; Here, in terms of molar fraction, the amount of hydrogen ligand used is 0.5 to 5% of the ionic liquid, the amount of strengthening agent used is 0.5 to 10% of the ionic liquid, and the amount of retention aid used is 0.5 to 5% of the ionic liquid.

[0009] Through the research of this application, it has been discovered that cellulose materials can be prepared using a composite ionic liquid dissolution system consisting of an ionic liquid, a hydrogen ligand, a strengthening agent and a retention agent system, and the viscosity of the dissolution system is low, the dissolution effect is high, and the mass fraction of cellulose dissolved in the system can be improved. The composite ionic liquid dissolution system is inexpensive, recyclable and has high feasibility.

[0010] The regenerated cellulose material has a smooth surface, few structural defects, and high material strength. Based on this material, the cellulose-based moisture-sensitive material can be produced by direct immersion method, which is simple and low cost.

[0011] In a second aspect of the present invention, there is provided a cellulosic moisture-sensitive color-changing material produced by the above method, the color-changing material changing from blue to red as humidity increases from 0% to 97% RH.

[0012] A natural cellulose material is dissolved in a composite ionic liquid dissolving system to obtain a cellulose solution, which is then regenerated in a coagulation bath, and the cellulose material is modified during the regeneration process to obtain a moisture-sensitive color-changing cellulose material, including cellulose fiber, cellulose film, cellulose gel, etc. The moisture-sensitive color-changing cellulose material can be adjusted according to the different humidity levels that need to be detected, and can be used for humidity detection and property evaluation in multiple fields such as electronics, medicine, materials, energy, etc., such as breath detection, diaper detection, sealed food detection, etc., with a wide range of applications and broad application prospects.

[0013] In a third aspect of the present invention, there is provided use of the above-mentioned cellulose-based moisture-sensitive color-changing material in the fields of electronics, medicine, materials, and energy. Effect of the Invention

[0014] The beneficial effects of the present invention are as follows: (1) The present invention uses a composite ionic liquid dissolution system to dissolve softwood kraft pulp, so that in the cellulose regeneration process, the cellulose is combined with hydrogen ligands, strengthening agents, retention agents, etc., thereby enhancing the physical strength of the cellulose material. (2) The cellulose-based moisture-sensitive color-changing material produced by the present invention has the advantages of high sensitivity, remarkable color-changing effect, high strength, high elongation, and high flexibility, and can be widely used for various raw materials such as hardwood kraft pulp, cotton pulp, bamboo pulp, and softwood dissolving pulp. (3) The cellulose-based moisture-sensitive color-changing material prepared by the present invention has a controllable moisture-sensitive range, and can accurately detect different ranges of humidity by adjusting simple processes according to usage needs. The color change can be from blue to red, and the change is remarkable and easy to observe. (4) The treatment method of the present invention is simple, highly practical, easy to spread, decomposes materials, and is easy to produce industrially. [Brief description of the drawings]

[0015] The drawings in the specification which form a part of the present invention are intended to provide a further understanding of the present invention, and the illustrative embodiments of the present invention and the description thereof are intended to provide an understanding of the present invention and are not intended to unduly limit the present invention.

[0016] [Figure 1] Color change of the comparative sample at humidities of 11% RH, 33% RH, 67% RH and 97% RH. [Diagram 2] Color change of the sample of Example 2 at humidities of 11% RH, 33% RH, 67% RH and 97% RH. [Diagram 3] 4. Color change of the sample of Example 3 at humidities of 11% RH, 33% RH, 67% RH and 97% RH. [Figure 4] 4 shows the viscosity of cellulose solutions of the comparative sample and the sample of Example 3. [Diagram 5] 1 shows SEM images of fiber cross sections of a comparative sample (left) and a sample of Example 3 (right). [Figure 6] 3 shows infrared spectra of a sample of a comparative example, a sample of an example 1, and a sample of an example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Please note that the following detailed description is all illustrative and is intended to further explain the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs.

[0018] As described in the background art, most of the current moisture-sensitive materials are non-degradable compounds, and the manufacturing process is complicated, and bio-based moisture-sensitive materials have low strength and low sensitivity.Therefore, the present invention provides a method for manufacturing a cellulose-based moisture-sensitive color-changing material.The method is to use softwood kraft pulp as raw material, dissolve it in a composite ionic liquid dissolving system, and then use an extruder or film applicator to produce different states of cellulose materials, and then immerse it in a coagulation bath to regenerate it.In the washing process, the obtained cellulose wet material is immersed in an appropriate concentration of cobalt chloride aqueous solution, and then dried to obtain a cellulose-based moisture-sensitive color-changing material, thereby obtaining a highly efficient and low-cost cellulose-based moisture-sensitive color-changing material, and at the same time, the material can be decomposed.

[0019] The experiment includes the following detailed steps. Ionic liquid, hydrogen ligand, strengthening agent and retention agent are mixed to synthesize a composite ionic liquid dissolving system. The softwood kraft pulp and composite ionic liquid dissolving system are mixed in a high-speed mixer at 60 to 75° C. for 20 to 30 minutes under vacuum until the cellulose is dissolved, to obtain a cellulose solution. The cellulose solution is poured into an extruder equipped with a metering device, spun or formed into a film, and the cellulose solution passes through a spinneret into a coagulation bath to obtain a cellulose wet fiber or a cellulose wet film. The obtained wet cellulose material is washed, immersed in an aqueous cobalt chloride solution for 10 to 60 s, dried, and curled to obtain a cellulose-based moisture-sensitive color-changing material.

[0020] In some embodiments, the mixing step of the dissolution system includes mixing the hydrogen ligand, the strengthening agent and the retention agent with the ionic liquid, heating and stirring to mix uniformly, and simultaneously heating the composite ionic liquid dissolution system to 60-75° C. for use. The amount of the hydrogen ligand is 0.5-5% (molar fraction) of the ionic liquid, the amount of the strengthening agent is 0.5-10% (molar fraction) of the ionic liquid, and the amount of the retention agent is 0.5-5% (molar fraction) of the ionic liquid.

[0021] In some embodiments, the softwood kraft pulp is a disintegrated and dispersed pulp having a moisture content of about 10%.

[0022] In the present application, the moisture content of the pulp is not particularly limited, and in some embodiments, the moisture content of the softwood kraft pulp is 6% to 15%, which can effectively shorten the dissolution time of cellulose in the dissolution system.

[0023] In some embodiments, the amount of softwood kraft pulp used is 8-15% (mass fraction) of the dissolution system, and the softwood kraft pulp and the composite ionic liquid dissolution system are premixed and then added to a 1L kneader for dissolution, the stirring speed is 100 rpm, the temperature is 70-80°C, and the dissolution time is generally 30-60 minutes.

[0024] In some embodiments, the dissolved cellulose solution is poured into an extruder for spinning or film formation, the aspect ratio of the screw is 20:1-30:1, the screw rotation speed is 50-60 rpm, the spinning nozzle is a vertical single-hole spinneret made of brass with a diameter of 0.6 mm-0.8 mm, the film formation die is a two-piece nozzle made of alloy material with a gap of 0.1 mm-1 mm, and the extrusion method is dry jet wet spinning.

[0025] In the present application, the rotation speed of the extruder, the hole diameter of the spinneret and the gap of the film-forming die are not particularly limited, and only affect the morphology of the fibers and films.

[0026] In some examples, the extruded cellulose solution falls vertically into the coagulation bath, the air gap is 10mm-30mm, the concentration of the composite ionic liquid dissolution system in the coagulation bath is 0%-20%, and the temperature is 20-30°C.

[0027] In the present application, the concentration of the coagulation bath is not particularly limited, and in some embodiments, the concentration of the coagulation bath has a certain effect on the strength of the regenerated fiber, and as the concentration of the coagulation bath increases, the fiber strength increases and, when it increases to a certain extent, begins to decrease.

[0028] In some embodiments, the coagulation bath is an aqueous system consisting of water and 1-allyl-3-methylimidazolium chloride, where the weight ratio of water to 1-allyl-3-methylimidazolium chloride is 9:1 or 8:2.

[0029] In some embodiments, the coagulated cellulosic material enters a washing tank to remove the composed ionic liquid.

[0030] In some embodiments, the cellulosic material after soaking and washing is placed in a soaking tank, the concentration of cobalt chloride in the soaking tank is 2% to 25% (mass fraction), the soaking time is 10 to 60 s, and the material is dried and curled to obtain a cellulosic moisture-sensitive color-changing material.

[0031] Another embodiment of the present invention provides a cellulosic moisture-sensitive color-changing material obtainable by the above method.

[0032] The cellulosic moisture-sensitive color-changing material provided by the present invention can display red or blue colors at different humidity levels.

[0033] The present invention will now be described in more detail with reference to specific examples, and it should be noted that the specific examples are for illustration rather than for limitation of the present invention.

[0034] Comparative Example: (1) 150 g of 1-allyl-3-methylimidazolium chloride (water content 0.72%) was mixed uniformly, and the dissolution system was simultaneously heated to 80° C. in preparation for use. (2) Softwood kraft pulp was disintegrated and dispersed, and the moisture content was approximately 9.7%. (3) 15.21 g of softwood kraft pulp and the dissolving system were premixed and then added to a 500 ml kneader and dissolved at a stirring speed of 60 rpm, a temperature of 75°C, and a dissolving time of 30 min. (4) The dissolved cellulose solution was poured into an extruder and spun. The aspect ratio of the screw was 27:1, the screw rotation speed was 60 rpm, the extrusion nozzle was a vertical single-hole spinneret made of brass with a diameter of 0.6 mm, and the extrusion method was dry jet wet spinning. (5) The cellulose solution extruded from the spinneret fell vertically into the coagulation bath with an air gap of 15 mm. Water was used in the coagulation bath and the temperature of the coagulation bath was 25°C. (6) The coagulated fiber entered into a washing tank to remove the ionic liquid, the length of the washing tank was 1 m, the washing liquid was distilled water, and the temperature of the washing tank was 60 °C. (7) The obtained wet cellulose material was placed in an immersion tank, the length of the immersion tank was 0.5 m, the immersion liquid was distilled water, the temperature of the immersion tank was 25° C., and the immersion time was 30 s. (8) After the soaking process, the cellulose material was dried with hot air (120°C, 2 min), and the dried fibers were curled onto a winding disc. The ratio of the linear speed of the winding disc to the extrusion speed was 1:1.

[0035] Example 1 The specific steps of the method for producing the cellulose-based moisture-sensitive color-changing material are as follows: (1) 1.86 g of triethylene glycol, 3.96 g of choline chloride, and 0.8 g of nanosilica were added to 159.32 g of 1-allyl-3-methylimidazolium chloride (water content: 0.47%) that was being slowly stirred, and then mixed uniformly at high speed and subjected to ultrasonic vibration for 10 min. At the same time, the dissolution system was heated to 70°C in preparation for use. (2) 17.15 g of softwood kraft pulp (moisture content 9.8%) and the composite ionic liquid system were premixed and then stirred under vacuum at a stirring speed of 60 rpm, a temperature of 70°C, and a dissolution time of 30 min. (3) The dissolved cellulose solution was poured into an extruder, the screw aspect ratio was 23:1, the screw rotation speed was 56 rpm, and 20 g of the extruded solution was placed into a square mold, the mold was square, the dimensions were 10 cm × 10 cm, the material was glass, and the surface of the solution was flattened using a film scraper. (4) A square mold was placed horizontally in the coagulation bath, the air gap was 15 mm, water was used in the coagulation bath, and the temperature of the coagulation bath was 25°C. (5) The coagulated cellulose film was entered into a washing tank to remove the ionic liquid, the length of the washing tank was 1 m, the washing liquid was distilled water, and the temperature of the washing tank was 60 °C. (6) The obtained wet cellulose film was placed in an immersion tank. The length of the immersion tank was 0.5 m, the immersion liquid was a 2.5% (mass fraction) cobalt chloride solution, the temperature of the immersion tank was 25°C, and the immersion time was 30 s. (7) After the immersion treatment, the cellulose film was dried with hot air (120°C, 2 min), and the peripheral stretch ratio during drying was 1:1.

[0036] Example 2 The specific steps of the method for producing the cellulose-based moisture-sensitive color-changing material are as follows: (1) 2.12 g of triethylene glycol, 4.05 g of choline chloride, and 1.08 g of nanocellulose fibrils were added to 150.34 g of 1-allyl-3-methylimidazolium chloride (water content 0.47%) and 12.29 g of 1-butyl-3-methylimidazolium chloride while slowly stirring, and mixed uniformly. At the same time, the dissolution system was heated to 70°C and prepared for use. (2) 18.47 g of softwood kraft pulp (moisture content 9.8%) and the composite ionic liquid system were premixed and then stirred under vacuum at a stirring speed of 80 rpm, a temperature of 70°C, and a dissolution time of 30 min. (3) The dissolved cellulose solution was poured into a single-screw extruder and spun. The aspect ratio of the screw was 26:1, the screw rotation speed was 60 rpm, the five temperature zones from the feed port to the extrusion port were 90°C, 170°C, 165°C, 130°C, and 120°C, the extrusion nozzle was a vertical single-hole spinneret made of brass with a diameter of 0.7 mm, and the extrusion method was dry jet wet spinning. (4) The cellulose solution extruded from the spinneret fell vertically into the coagulation bath with an air gap of 20 mm. The coagulation bath used an aqueous solution system consisting of water / 1-allyl-3-methylimidazolium chloride, with a mass ratio of water to 1-allyl-3-methylimidazolium chloride of 9:1, and the temperature of the coagulation bath was 25°C. (5) The coagulated fiber entered into a washing tank to remove the ionic liquid, the length of the washing tank was 1 m, the washing liquid was distilled water, and the temperature of the washing tank was 60 °C. (6) The obtained wet cellulose film was placed in an immersion tank. The length of the immersion tank was 0.5 m, the immersion liquid was a 2.5% (mass fraction) cobalt chloride solution, the temperature of the immersion tank was 25°C, and the immersion time was 30 s. (7) After the soaking was completed, the cellulose was dried with hot air (120°C, 2 min), and the dried fiber was curled onto a winding disk. The speed ratio between the linear speed of the winding disk and the extrusion speed was 1:1.

[0037] Example 3 The specific steps of the method for producing the cellulose-based moisture-sensitive color-changing material are as follows: (1) 2.86 g of urea, 3.98 g of choline chloride, and 0.4 g of nanocellulose were added to 158.32 g of 1-allyl-3-methylimidazolium chloride (water content 0.47%) with slow stirring, and stirred at high speed at 80°C for 15 min. At the same time, the dissolution system was heated to 70°C and prepared for use. (2) 16.93 g of softwood kraft pulp (moisture content 9.8%) and the composite ionic liquid system were premixed and then stirred under vacuum at a stirring speed of 60 rpm, a temperature of 70°C, and a dissolution time of 30 min. (3) The dissolved cellulose solution was poured into a single-screw extruder and spun. The aspect ratio of the screw was 26:1, the screw rotation speed was 50 rpm, the five temperature zones from the feed port to the extrusion port were 85°C, 170°C, 165°C, 130°C, and 120°C, the extrusion nozzle was a vertical single-hole spinneret made of brass with a diameter of 0.6 mm, and the extrusion method was dry jet wet spinning. (4) The cellulose solution extruded from the spinneret fell vertically into the coagulation bath with an air gap of 10 mm. The coagulation bath used an aqueous solution system consisting of water / 1-allyl-3-methylimidazolium chloride, with a mass ratio of water to 1-allyl-3-methylimidazolium chloride of 8:2, and the temperature of the coagulation bath was 30°C. (5) The coagulated fiber entered into a washing tank to remove the ionic liquid, the length of the washing tank was 1 m, the washing liquid was distilled water, and the temperature of the washing tank was 60 °C. (6) The obtained wet cellulose film was placed in an immersion tank. The length of the immersion tank was 0.5 m, the immersion liquid was a 5.0% (mass fraction) cobalt chloride solution, the temperature of the immersion tank was 30°C, and the immersion time was 25 s. (7) After the soaking was completed, the cellulose was dried with hot air (120°C, 2 min), and the dried fiber was curled onto a winding disc. The ratio of the linear speed of the winding disc to the extrusion speed was 1.1:1.

[0038] Experimental Testing: The performance of the cellulose-based moisture-sensitive color-changing materials produced in the Comparative Example and Examples 1 to 3 was tested, and the specific test method was as follows. Moisture-sensitive discoloration test: 100 ml of solution was prepared in a 250 ml wide-mouthed reagent bottle. Under relative humidity environments of 11%, 33%, 67%, 87% and 97%, a cellulose-based moisture-sensitive discoloration material was placed 5 cm above the liquid surface and allowed to stand for 5 minutes before observing the color change. Moisture-sensitive electrical response test. In a 250ml wide-mouthed reagent bottle, 100ml of solution was prepared under the relative humidity environments of 11%, 33%, 67%, 87% and 97%, the electrodes of the electrochemical workstation were clamped on both ends of the cellulose-based moisture-sensitive color-changing material, with a distance of 1cm between them, and the cellulose-based moisture-sensitive material was placed 5cm above the liquid surface. The change in resistance was recorded using an electrochemical workstation (manufactured by Shanghai Chenhua Company, model number CHI760E) and a computer. Breaking strength and breaking elongation: The equipment used was a texture analyzer manufactured by Stable Microsystems, model number PL / CEL5, and the test method was in accordance with GBT14337-2008. The results are shown in Table 1. The viscosity of the cellulose / ionic liquid solution was measured using an ES-G2 rotational rheometer (TA Instruments, New Castle, USA) with parallel plates of 20 mm diameter. The gap was 1 mm for all measurements. The shear rate range was 0.1–100 s -1 and the scanning angular frequency (w) was 6.28 rad / s. Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS). SEM testing uses a Schottky field emission electron gun, the resolution is 0.9nm@15Kv (secondary electron image), 2.0nm@30Kv (backscattered electron image), the electron optical path is a non-crossing optical path in the microscope tube, the acceleration voltage is 200v~30kv, the probe beam is 1pA~100nA, the stability is better than 0.2% / h, the magnification is 8x~100,000x, the objective lens uses an electromagnetic / electrostatic composite lens, the detectors are: In-Beam SE and SE secondary electron detector, backscattered detector, EDS energy dispersive X-ray spectrometer. The model number of the EDS energy dispersive X-ray spectrometer is Xplore 30, the working distance of the energy dispersive X-ray analysis is 15 mm, and the sample stage stroke is X=125 mm, Y=125 mm, Z=50 mm, T=-60°~60°, R=360°(continuously adjustable). Before testing the samples, the gold spray stage was used to spray gold on the surface and cross section of the fibers to improve their electrical conductivity.

[0039] An ALPHA FTIR spectrophotometer for infrared analysis (Bruker Corporation, Billerica, MA, USA) was used to record the Fourier transform infrared (FTIR) spectra of the regenerated cellulose fibers, measured in attenuated total reflection (ATR) mode, and the probe was a diamond-ZnSe crystal. The wavelength range was 500–4000 cm. -1 , resolution is 4cm -1 Ten closely spaced fibers were tested under the probe, and each sample was repeated at least three times. All spectra were air-corrected, water vapor-corrected, auto-baseline-corrected, MONIC 9.0 software smoothed, and free of ATR correction.

[0040] [Table 1]

[0041] 1-3 show the color changes of the samples produced in Comparative Example, Example 2, and Example 3 under 11% RH, 33% RH, 67% RH, and 97% RH humidity, respectively. From FIG. 1-FIG. 3 and Table 1, it can be seen that the cellulose fibers subjected to the cobalt chloride immersion treatment show different colors under different humidities compared to the Comparative Example, and among them, the sample of the Comparative Example did not change color under 11% RH, 33% RH, 67% RH, and 97% RH humidity (shown in FIG. 1). The sample of Example 2 is dark blue at 11% RH, light blue at 33% RH, purple at 67% RH, and red at 97% RH (shown in FIG. 2). The sample of Example 3 is cyan blue at 11% RH, dark blue at 33% RH, light blue at 67% RH, and red at 97% RH (shown in FIG. 3). As the relative humidity increases, the cellulose material gradually changes from blue to red, and the humidity response time of Example 1 is 367 s, the humidity response time of Example 2 is 380 s, and the humidity response time of Example 3 is 248 s, and all examples have good color change response and electrical response.

[0042] From the data in Table 1, it can be seen that the strength of the regenerated fiber that was soaked in cobalt chloride after adding choline chloride and polyhydric alcohol is significantly improved compared to the strength of the regenerated cellulose fiber that was not added. The breaking strength of the comparative example was 58.43 MPa, and the breaking elongation was 15.23%, the breaking strength of the example 1 was 153.32 MPa, an increase of 162.40%, and the breaking elongation was 10.34%, the breaking strength of the example 2 was 150.36 MPa, an increase of 157.16%, and the breaking elongation was 8.73%, and the breaking strength of the example 3 was 132.37 MPa, an increase of 126.54%, and the breaking elongation was 4.23%. The manufacturing method of the cellulose-based moisture-sensitive color-changing material of the present invention can also improve the strength of the cellulose material.

[0043] Figure 4 shows the viscosity of the cellulose solution of the comparative sample and the sample of Example 3. From Figure 4, it can be seen that the viscosity of the cellulose solution of Example 3 is significantly lower than that of the comparative sample, which shows that the composite ionic liquid dissolution system consisting of ionic liquid, hydrogen ligand, strengthening agent and retention agent system is used to produce cellulose material, and the viscosity of the dissolution system is low, the dissolution effect is high, and the mass fraction of cellulose dissolved in the system can be improved.

[0044] Figure 5 shows the cross-sectional SEM images of the samples of the comparative example and Example 3. The inside of the comparative example sample shows a large pore structure, with the pore size and shape not consistent, while the diameter of the pore structure of the cross-section of the moisture-sensitive discoloring cellulose fiber prepared by the composite ionic liquid dissolution system is significantly smaller, and at the same time the pores are regularly arranged. The cross-sectional SEM images show that the cellulose structure inside the fiber prepared by this patent is more densely and uniformly arranged, which improves the strength of the regenerated cellulose fiber.

[0045] Fig. 6 shows infrared spectra of the sample of the comparative example, the sample of the example 1, and the sample of the example 3. As shown in Fig. 6, choline chloride can be used as a retention agent in the production of a cellulose-based moisture-sensitive discoloration material, and the infrared spectrum of the sample of the comparative example, which is in the wavelength range of 2920 to 2885 cm -1 The peaks at 1425 cm are considered to be characteristic peaks of -CH and CH stretching bonds of cellulose, and the characteristic wavelengths of the samples of Example 1 and Example 3 change therein, where the -CH stretching bond is blue-shifted and the -CH stretching bond is red-shifted. -1 The -CH2 bend bond in was slightly shifted, and such treatment altered the chemical environment of the hydroxymethyl group attached to C6 in the glucose unit, evidence of the presence of the retention agent choline chloride in the cellulosic material.

[0046] The above is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Those skilled in the art can make various modifications and changes to the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A method for producing a cellulose-based moisture-sensitive color-changing material, comprising the steps of: The paper pulp and the composite ionic liquid dissolving system are mixed under vacuum at 60 to 75° C. for 20 to 30 minutes to dissolve the cellulose, thereby obtaining a cellulose solution; regenerating the cellulose solution to obtain a cellulose wet material; and immersing the cellulose wet material in an aqueous cobalt chloride solution having a concentration of 2 wt % to 25 wt % for 10 to 60 s and drying the same to obtain the cellulose-based moisture-sensitive color-changing material. The composite ionic liquid dissolution system includes an ionic liquid, a hydrogen ligand, a strengthening agent, and a retention agent; A method for producing a cellulose-based moisture-sensitive color-changing material, characterized in that the amount of the hydrogen ligand used is 0.5 to 5% of the ionic liquid, the amount of the strengthening agent used is 0.5 to 10% of the ionic liquid, and the amount of the retention agent used is 0.5 to 5% of the ionic liquid, in terms of molar fraction.

2. 2. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 1, wherein the ionic liquid is an imidazolium-based ionic liquid.

3. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 2, characterized in that the ionic liquid is selected from at least one of 1-allyl-3-methylimidazolium chloride, 1-allyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium chloride and 1-ethyl-3-methylimidazolium acetate.

4. 2. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 1, wherein the hydrogen ligand is a hydrogen bond donor selected from at least one of urea, ethylene glycol, and glycerin.

5. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 1, characterized in that the reinforcing agent is at least one of nanocellulose fibrils, nanocellulose fibers, and nanosilica.

6. 2. The method for producing a cellulose-based moisture-sensitive discoloration material according to claim 1, wherein the retention agent is choline chloride.

7. The method for producing the cellulose-based moisture-sensitive color-changing material according to claim 1, characterized in that the step of preparing the composite ionic liquid dissolving system is to mix hydrogen ligand, strengthening agent and retention agent with ionic liquid, heat and stir to uniformly mix, and simultaneously heat the composite ionic liquid dissolving system to 60-75°C.

8. 2. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 1, wherein the amount of the paper pulp used is 8 to 15 wt % of the composite ionic liquid dissolving system.

9. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 1, characterized in that the dissolved cellulose solution is poured into an extruder and spun or film-formed, the aspect ratio of the screw of the extruder is 20:1-30:1, the screw rotation speed is 50-60 rpm, the spinning extrusion nozzle is a vertical single-hole spinneret made of brass with a diameter of 0.6 mm-0.8 mm, the film-forming mold is a two-piece nozzle made of alloy material with a gap of 0.1 mm-1 mm, and the extrusion method is dry jet wet spinning.

10. The method for producing a cellulose-based moisture-sensitive color-changing material according to claim 9, characterized in that the extruded cellulose solution falls vertically into the coagulation bath, the air gap is 10mm-30mm, the concentration of the composite ionic liquid dissolving system in the coagulation bath is 0%-20%, and the temperature is 20-30°C.

11. 2. The method for producing a cellulose-based moisture-sensitive discoloring material according to claim 1, wherein the paper pulp is softwood kraft pulp, hardwood kraft pulp, cotton pulp, bamboo pulp or softwood dissolving pulp.

12. A cellulose-based moisture-sensitive color-changing material produced by the method according to any one of claims 1 to 11.

13. Use of the cellulose-based moisture-sensitive color-changing material according to claim 12 in electronics, medicine, materials and energy.

14. 14. The use according to claim 13, characterized in that the cellulosic moisture-sensitive color-changing material is used for humidity detection.

Citation Information

Patent Citations

  • Humidity-sensitive electrospun cobalt chloride micro-nanofiber membrane as well as preparation method and application thereof

    CN105568557A

  • Flame-retardant regenerated cellulose fiber and preparation method thereof

    CN110938885A

  • Preparation method of high-strength regenerated cellulose fibers

    CN113481619A

  • Nanofiber colorimetric humidity sensor and preparation method thereof

    CN114441527A

  • Method for improving surface structure of regenerated cellulose fiber

    CN114775087A